Risk Management in Operations: From Identification to Mitigation Strategies in Complex Global Supply Networks - Latunreng, Wahyuddin (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This study investigates the key factors influencing risk in global supply network operations, with a particular focus on demand uncertainty. The research objective is to identify the factors that cause uncertainty in product demand in a global supply network environment and to evaluate the implications of this uncertainty for the company's operational performance. The research method used is a systematic literature review using the Scopus database to collect relevant articles. The results show that fluctuations in consumer behavior, macroeconomic factors, and global market interconnectedness are the main factors influencing demand uncertainty in the global supply network. The implication of this research is that it is important for companies to develop strategies that are adaptive and responsive to changes in global market demand to improve their operational performance and resilience.